2018
DOI: 10.21837/pmjournal.v16.i5.408
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Virtual Urban Environments: a Preliminary Investigation

Abstract: Virtual reality (VR) technologies enable users to be virtually immersed in reconstructed cities and streets from around the globe. Immersive technologies could provide users a suggestive sensation of “being there” in a reconstructed virtual urban environments (VUE). This research argues that experiential VUE could promote better understanding of a place while offering unique interactions within its surrounding elements. The aim of this research is to present a preliminary study of the factors determining place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The emotional dimension is therefore a result of the other two dimensions; the behavioural and the cognitive. (Ghani et al 2018). The heterogeneous spatial structure and the abundance of green open spaces in the TiB provides great potential for people to strengthen their relationship with the natural environment and participate in various kinds of stewardship activities such as restoration, cleaning, and maintenance activities.…”
Section: Sense Of Placementioning
confidence: 99%
“…The emotional dimension is therefore a result of the other two dimensions; the behavioural and the cognitive. (Ghani et al 2018). The heterogeneous spatial structure and the abundance of green open spaces in the TiB provides great potential for people to strengthen their relationship with the natural environment and participate in various kinds of stewardship activities such as restoration, cleaning, and maintenance activities.…”
Section: Sense Of Placementioning
confidence: 99%
“…Schnabel (2004) focuses on how VR can improve spatial understanding. Ghani et al (2018) have identified six key elements required for creating an effective VR experience for architectural and urban models: 1) contextual setting, 2) interactivity, 3) navigation, 4) level of detail (LOD), 5) viewpoints, and 6) auditory environment. Kim and Kim (2019) use VR as a way of evaluating urban spaces, exploring the ratio of the depth-to-height of virtual models of urban spaces.…”
Section: Introductionmentioning
confidence: 99%
“…To unleash the full potential of the Metaverse, besides the 3D representation and digitization of the urban space, further components are required. Ghani et al (2018) consider interactivity, contextual setting, and auditory capabilities among the elements required for an experiential virtual urban environment. Ning et al (2021) deem the interactivity, in particular, as one of the open issues in the Metaverse domain.…”
mentioning
confidence: 99%